Anti-Haemophilus Activity of Selected Essential Oils Detected by TLC-Direct Bioautography and Biofilm Inhibition - Balázs Viktória Lilla (MOLECULES, 2019)
Essential oils (EOs) are becoming increasingly popular in medical applications because of their antimicrobial effect. Direct bioautography (DB) combined with thin layer chromatography (TLC) is a screening method for the detection of antimicrobial compounds in plant extracts, for example, in EOs. Due to their lipophilic character, the common microbiological assays (etc. disk diffusion) could not provide reliable results. The aim of this study was the evaluation of antibacterial and anti-biofilm properties of the EO of cinnamon bark, clove, peppermint, thyme, and their main components against Haemophilus influenzae and H. parainfluenzae. Oil in water (O/W) type Pickering nano-emulsions stabilized with silica nanoparticles from each oil were prepared to increase their water-solubility. Samples with Tween80 surfactant and absolute ethanol were also used. Results showed that H. influenzae was more sensitive to the EOs than H. parainfluenzae (except for cinnamon bark oil). In thin layer chromatography-direct bioautography (TLC-DB) the ethanolic solutions of thyme oil presented the best activity against H. influenzae, while cinnamon oil was the most active against H. parainfluenzae. Pickering nano-emulsion of cinnamon oil inhibited the biofilm formation of H. parainfluenzae (76.35%) more efficiently than samples with Tween80 surfactant or absolute ethanol. In conclusion, Pickering nano-emulsion of EOs could inhibit the biofilm production effectively.